A Maximally Flat Group Delay Recursive Digital Filter with Improved Passband Magnitude Response - Thajchayapong, P.; Cheevasuvit, F. (My University, 1979)
A technique is proposed for the design of a recursive digital filter with maximally flat responses in both magnitude and group delay. In comparison to the previous designs [1] -[3], the magnitude and group delay always show smooth responses no matter what the difference is in the polynomial degrees of the numerator and denominator. Copyright © 1979 by The Institute of Electrical and Electronics Engineers, Inc.